Subwavelength InSb-based Slot wavguides for THz transport: concept and practical implementations - Ma, Youqiao; Zhou, Jun; Pištora, Jaromír; Eldlio, Mohamed; Nguyen-Huu, Nghia; Maeda, Hiroshi; Wu, Qiang; Cada, Michael (Scientific reports, 2016)
Seeking better surface plasmon polariton (SPP) waveguides is of critical importance to construct the frequency-agile terahertz (THz) front-end circuits. We propose and investigate here a new class of semiconductor-based slot plasmonic waveguides for subwavelength THz transport. Optimizations of the key geometrical parameters demonstrate its better guiding properties for simultaneous realization of long propagation lengths (up to several millimeters) and ultra-tight mode confinement (~λ2/530) in the THz spectral range. The feasibility of the waveguide for compact THz components is also studied to lay the foundations for its practical implementations. Importantly, the waveguide is compatible with the current complementary metal-oxide-semiconductor (CMOS) fabrication technique. We believe the proposed waveguide configuration could offer a potential for developing a CMOS plasmonic platform and can be designed into various components for future integrated THz circuits (ITCs).